2005
DOI: 10.1097/01.pec.0000173344.30401.8e
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Bedside Ultrasound and Patient Perception in Detecting Soft Tissue Foreign Bodies in Children

Abstract: Bedside US is comparable to the performance of radiography interpreted by an attending pediatric radiologist. Bedside US alone or combined with patient perception may be an adequate initial screening tool for detecting wound FBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…The reported rate of traumatic or failed LPs in children is between 10 and 50%, depending on patient age and the red blood cell (RBC) count used to define "traumatic." [1][2][3][4][5][6][7] Bedside point-of-care ultrasound is used by emergency physicians to facilitate the performance of a variety of procedures, including the presence and need for reduction of long-bone fractures, 7 detection of foreign bodies, 8 successful collection of urine specimens, 9 and central line placement. 10 A prospective randomized controlled trial in adults documented the beneficial effect of ultrasound-assisted lumbar puncture (UALP).…”
mentioning
confidence: 99%
“…The reported rate of traumatic or failed LPs in children is between 10 and 50%, depending on patient age and the red blood cell (RBC) count used to define "traumatic." [1][2][3][4][5][6][7] Bedside point-of-care ultrasound is used by emergency physicians to facilitate the performance of a variety of procedures, including the presence and need for reduction of long-bone fractures, 7 detection of foreign bodies, 8 successful collection of urine specimens, 9 and central line placement. 10 A prospective randomized controlled trial in adults documented the beneficial effect of ultrasound-assisted lumbar puncture (UALP).…”
mentioning
confidence: 99%
“…30 This study reported a sensitivity of 66.7% (95% CI = 34.8% to 90.1%) and a specificity of 96.6% (95% CI = 91.6% to 99.1%). Four studies 24,28,31,33 took place in the general ED setting, one in a pediatric ED, 30 and two in orthopedic EDs. 25,26 Our meta-analysis yielded overall sensitivity and specificity of 72% (95% CI = 57% to 83%) and 92% (95% CI = 88% to 95%), respectively ( Figure 2).…”
Section: Resultsmentioning
confidence: 78%
“…After our complete review of these articles and their reference sections and our limited reviews of other databases, we included 17 articles in this metaanalysis (Table 1). All 17 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] reported data for calculation of sensitivity; however, only 13 [23][24][25][26][27][28][29][30][31][32][33][34]36,37 reported data for calculation of specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24] Therefore, it is important that pediatric EPs be appropriately trained in its use. Ours is the first study to evaluate emergency EUS training for pediatric EPs.…”
Section: Discussionmentioning
confidence: 99%